USING COMMUNICATION THEORY - Olson Jean T; Signitzer Benno; Windahl Sven (Sage Publications, 1992)
THE BASICS THEORETICAL APPROACHES TO CUMMUNICATION PLANNING THE ELEMENTS OF MASS COMMUNICATION THEORY
THE BASICS THEORETICAL APPROACHES TO CUMMUNICATION PLANNING THE ELEMENTS OF MASS COMMUNICATION THEORY